Sistem Prediksi Jumlah Permintaan Produk Darah Menggunakan Metode Least Square Regression Line (Studi Kasus : Utd Pmi Kabupaten Jombang) - Dzurrotun Nasyika; Slamin Slamin; Priza Pandunata (Faculty of Computer Science, University of Jember, 2018)
Blood Transfusion Unit (UTD) as the provider of blood supply is required to fulfill blood demand. However in reality, the blood stock does not always meet the demand for blood. The amount of blood group stock in UTD depends on blood donors who voluntarily donate blood. Red blood cells only have a life span of 35 days since they were donated, if they have passed that time the blood cannot be used for transfusion. Based on these problems, the authors applied the Lesat Square Regression Line method to predict the number of requests for blood products in the coming month. The calculation results obtained prediction of demand with the smallest MAPE value that is blood product of PRC blood type A with a value of 14.40%. The biggest MAPE value obtained is 180.66% for WB blood type AB. Factors or parameters that affect the amount of blood product demand, that is the environment, disease outbreaks and differences in body resistance of each blood group. In addition, the types of blood products also have a number of different requests depending on the level of blood needs for health.